Augmentation index and aortic stiffness in bicuspid aortic valve patients with non-dilated proximal aortas. - Warner, Patrick J.; Al-Quthami, Adeeb.; Brooks, Erica L.; Kelley-Hedgepeth, Alyson.; Patvardhan, Eshan.; Kuvin, Jeffrey T.; Heffernan, Kevin S.; Huggins, Gordon S. (2016)
Background: We compared aortic stiffness, aortic impedance and pressure from wave reflections in the setting of bicuspid aortic valve (BAV) to the tricuspid aortic valve (TAV) in the absence of proximal aortic dilation. We hypothesized BAV is associated with abnormal arterial stiffness.; Keywords: Bicuspid aortic valve, Arterial stiffness, Augmentation index, Pulse wave velocity.; Springer Open.